2018
DOI: 10.1016/j.jvs.2017.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers are not associated with endoleaks after endovascular repair of abdominal aortic aneurysms

Abstract: Circulating concentrations of MMP9, OPG, D-dimer, HCY, and CRP were not associated with endoleak in patients undergoing EVAR in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
(66 reference statements)
2
14
3
2
Order By: Relevance
“…MMPs and their endogenous TIMPs could not be extracted from aneurysmal aortic wall due to the small number of open cases in the study period. However, in contrast to previous studies reporting mean follow-up of 6 to 25 months (only 3 months for plasma MMP-9 assessment), 21,23,24,26 our mean follow-up period exceeded 5 years. Additionally, low-pressure type II endoleaks were excluded from the endoleak group (all sealed within follow-up), thus permitting us to focus on baseline circulating and tissue biomarkers that might be more elevated in patients who developed late endoleaks.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…MMPs and their endogenous TIMPs could not be extracted from aneurysmal aortic wall due to the small number of open cases in the study period. However, in contrast to previous studies reporting mean follow-up of 6 to 25 months (only 3 months for plasma MMP-9 assessment), 21,23,24,26 our mean follow-up period exceeded 5 years. Additionally, low-pressure type II endoleaks were excluded from the endoleak group (all sealed within follow-up), thus permitting us to focus on baseline circulating and tissue biomarkers that might be more elevated in patients who developed late endoleaks.…”
Section: Discussioncontrasting
confidence: 99%
“…A large study by Sangiorgi et al 25 also reported higher plasma MMP-9 concentrations in patients with endoleak (40.2±20.9 ng/mL) compared to no-endoleak controls (23.6±10.4 ng/mL). Similar to Moxon et al, 26 circulating concentrations of MMP-9 in patients with endoleak did not exceed those observed in no-endoleak subjects in our study. Evidence suggests that specific markers such as plasma MMP-9 may serve as valuable adjunctive diagnostic tools for detection of endoleak after EVAR, with a sensitivity and specificity of 100% and 96%, respectively, at a cutoff MMP-9 value of 55.18 ng/mL.…”
Section: Biomarker Concentrationssupporting
confidence: 92%
See 2 more Smart Citations
“…A leak back into an aneurysm sac is a relatively frequent event in patients with AAA following endovascular repair, and this complication can only be diagnosed by long-term follow-up including regular imaging of the aorta. It is worth noting that Moxon et al diagnosed this type of complication in patients with the largest diameter aneurysms (in 24 of 75 patients) [ 43 ]. The authors analyzed MMP-9 activity and serum concentrations of OPG, d -dimer, homocysteine and C-reactive protein as the possible indicators of leaks in patients with AAA undergoing endovascular aneurysm repair.…”
Section: Opg Concentrations Versus Aaamentioning
confidence: 99%